Buddha’s Ideas on the Origin of the State: A Comparative Study with Western Theories - Acharya, Tilak Ram (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
The origin of the states has been viewed differently ranging from social contract theories to divine creation. This research article explores the concept of the origin of the state in Buddhist philosophy, particularly as outlined in the Aggañña Sutta of the Dīgha Nikāya. It reviews existing scholarship associated with Buddhist political concepts against the divine theory and the social contract theory presented in the thoughts of John Locke, Thomas Hobbes and Jean-Jacques Rousseau. The paper conducts an in-depth evaluation of the Buddhist evolutionary perspective toward developing human communities alongside property management systems, family systems, and state institutions. It also conducts an in-depth evaluation using both primary and secondary resources to demonstrate how Buddhist theory about state development assists political philosophy and identify research gap so as to unfold point of departure in this article that differs from previous studies. Buddhist thought disagrees with divine theory because it explains creation by natural evolution. The Buddhist concept of governance exhibits close similarity to social contract theory because it promotes the idea that people have sovereignty rights.